Government of Singapore investment corporation (GIC): Insurer of last resort and bulwark of nation-state legitimacy. - Clark, G; Monk, A (Routledge, 2010)
The global financial crisis has shattered many illusions, one of which being that sovereign wealth funds (SWFs) are properly treated as arms-length investment institutions subject only to global standards of good governance. In fact, in a number of East Asian countries SWFs have acted as 'insurers of last resort' for their nation-states underwriting financial stability and social welfare. In this paper, we explain how and why this came to pass, arguing that this role serves to sustain the legitimacy of the nation-state as well as justify the separation of SWF assets from the public interest in current consumption and spending. Focusing upon the Government of Singapore Investment Corporation (GIC), we suggest that the prospect of recurrent financial crises was an important prompt for its establishment in 1981, reinforced by the experience of many East Asian countries in the 1997 Asian financial crisis. The formal constitution of the GIC, the mechanisms by which its reserves are returned to the government in crisis, and the role of different sections of the political elite in managing those assets are explained. Referencing the principles of best-practice fund governance and the Santiago Principles underwriting the legitimacy of SWFs, we also consider the governance of the GIC, especially as regards its investment processes. Implications are drawn for the experience of Western countries, particularly the UK and the USA, wherein the failure of their banking systems has put untold pressures on current and future living standards.